2015
DOI: 10.1021/acsnano.5b03791
|View full text |Cite
|
Sign up to set email alerts
|

Cleaning of Oil Fouling with Water Enabled by Zwitterionic Polyelectrolyte Coatings: Overcoming the Imperative Challenge of Oil–Water Separation Membranes

Abstract: Herein we report a self-cleaning coating derived from zwitterionic poly(2-methacryloyloxylethyl phosphorylcholine) (PMPC) brushes grafted on a solid substrate. The PMPC surface not only exhibits complete oil repellency in a water-wetted state (i.e., underwater superoleophobicity), but also allows effective cleaning of oil fouled on dry surfaces by water alone. The PMPC surface was compared with typical underwater superoleophobic surfaces realized with the aid of surface roughening by applying hydrophilic nanos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
179
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 298 publications
(181 citation statements)
references
References 63 publications
1
179
1
Order By: Relevance
“…Most of the materials fabricated using existing technologies can separate only one of the two fluids, and separating the other one requires a different technology151617181920212223242526272829303132333435363738. The possibility to selectively separate both fluids using the same material offers flexibility for different oil/water separation applications.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the materials fabricated using existing technologies can separate only one of the two fluids, and separating the other one requires a different technology151617181920212223242526272829303132333435363738. The possibility to selectively separate both fluids using the same material offers flexibility for different oil/water separation applications.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, multiple fabrication techniques and materials are used to realize seemingly similar oil/water separation tasks. For example, aerogels, powders, graphene oxide films, sponges modified with graphene, carbon nanotubes (CNT), nanoparticles or low-surface energy chemicals are used for oil absorption from water415161718192021222324; superhydrophobic CNT membranes, metal meshes or textiles chemically modified or coated with metal oxide nanoparticles and nanorods are utilized for oil filtration from oil/water mixtures25262728293031; and underwater superoleophobic porous nanotube membranes, meshes and textiles modified with palygorskite powders, zeolites, TiO 2 nanostructures, nanoparticles, zwitterionic polymers or cellulose aerogels are used for filtrating water from oil/water mixtures3233343536373839. To ensure a better control over the oil/water separation process, materials which switch their wetting properties in response to external stimuli such as changing electric or magnetic field, pH, temperature or light illumination, and pre-wetted materials were developed64041424344.…”
mentioning
confidence: 99%
“…This implied the surface of the DURA-Z coating had superior antifouling property as good as a zwitterionic hydrogel. [8] Water contact angle (Figure 2b) indicated that the DURA-Z coating was superhydrophilic with great wettability (the water drop spread out quickly as demonstrated by Movie S1 in the Supporting Information), similar to pure PCBAA hydrogel surface.…”
mentioning
confidence: 98%
“…Superhydrophilic zwitterionic polymer materials are known for their superior antifouling properties. [8] But they, like common hydrophilic coatings, drastically tend to dissolve in the aqueous environment resulting in poor coating durability. [9,10] The vulnerability to mechanical damages further prevents these hydrophilic coatings from being practically applied.…”
mentioning
confidence: 99%
“…In general, water is used to clean the fouled membrane surface. However, it is difficult to fully remove the organic materials of AEMs25. A current strategy for controlling membrane fouling is to cross-link an antifouling layer on the surface of the AEMs26272829.…”
mentioning
confidence: 99%